O processo de reprodução socioterritorial intergeracional do campesinato assentado em Sapé-PB - Panta, Rômulo Luiz Silva (2020)
In the last decades, a relevant and large collection of researches about the agrarian issue in Brazil has given special attention to the creation of rural settlements. These researches focus on settlements' several dimensions, focusing more specifically on the processes of territorialization and territory reform. Nevertheless, when the internal dynamics of Agrarian Reform's rural settlements is analyzed, it is verified that the access to the land, that is, the peasantry territorialization is only the first step in the process of peasant recreation. Indeed, the struggle for the survival and permanence of the peasants in the countryside does not end after the creation of settlements. In this sense, we present some challenges observed from the settlements' internal contradictions as the intergenerational peasant reproduction and its socio-territorial processes. Geography may contribute to the understanding of these contradictions. This research aims to analyze the socio-territorial and intergenerational peasantry reproduction process in the rural settlements of Agrarian Reform in Sape-PB, Brazil. Regarding the methodology, the proposal is oriented by the historical and dialectical materialism as a method of interpretation of reality. The territorial outline comprises six rural settlements of Agrarian Reform located in Sape-PB, Brazil (Santa Helena, Boa Vista, Rainha dos Anjos, 21 de abril, Nova vivência and Padre Gino). The study central category of analysis is the extended family, that is, the group formed by the nuclear beneficiary family of the agrarian politics and the families of sons and daughters that settled residency in the lot. Besides the bibliographic survey on the topic, fieldwork was also conducted. The first phase of direct research consisted of the data survey about all the extended families that reside in the six settlements. From this survey it was defined a sample correspondent to 30% of the extended families. Interviews were performed with these families and also with the directions of these settlements associations. In the study, we verified the settled peasantry process of intergenerational reproduction, the internal mechanisms of conformation of the intergenerational populational design, the territorial dynamics exercised by the extended segment and the tensions generated from the demographic pressure in the peasantry production units of family base. They were also investigated the multiple forms, relations and the adherence processes of the settled peasantry with the exploitation of the territory and the labor power by capital.